Questões metodológicas e ferramentas de pesquisa nos estudos em Aquisição da Linguagem - Hilário, Rosângela Nogarini; Del Ré, Alessandra (Letras de Hoje, 2015)
Este artigo visa a apresentar, de forma resumida, aspectos relacionados à metodologia voltada para uma abordagem dialógica e discursiva nos estudos em Aquisição da Linguagem. Nele discutimos quatro aspectos centrais envolvidos nessa temática: i) a relação entre a metodologia aplicada, as questões de pesquisas e a abordagem teórica, ii) algumas ferramentas de transcrição e análise disponíveis e a aplicação das mesmas aos estudos de cunho mais qualitativo, iii) as categorias de análise – linguísticas e discursivas, iv) a necessidade de (e a dificuldade em) comparar as produções da criança. Com isso, pretende-se introduzir na discussão acerca das escolhas metodológicas, as questões concernentes a uma abordagem que considera a relação entre língua e discurso. ************************************************************************************************************************************************************************************************************ Methodological questions and tools of research in Language Acquisition Abstract: This article aims to present, in summary, some aspects related to the methodology in a dialogical and discursive approach in Language Acquisition studies. It will be discussed four essential aspects involved in this topic: i) the relation between the applied methodology, the research questions and the theoretical approach, ii) some of the available transcription and analysis tools and their usage on qualitative studies, iii) the categories of analysis – linguistic and discursive, iv) the need (and the difficulty) to compare the children’s productions. Therefore, it is intended to introduce in the discussion about the methodological choices, the questions related to an approach which considers the relation between language and discourse. Keywords: Language Acquisition; Dialogical and discursive approach; Qualitative and quantitative researches